Health Insurance Expansion and Incidence of Out‐of‐Hospital Cardiac Arrest: A Pilot Study in a US Metropolitan Community. Issue 7 (28th June 2017) - Stecker, Eric C.; Reinier, Kyndaron; Rusinaru, Carmen; Uy‐Evanado, Audrey; Jui, Jon; Chugh, Sumeet S.
Abstract : Background: Health insurance has many benefits including improved financial security, greater access to preventive care, and better self‐perceived health. However, the influence of health insurance on major health outcomes is unclear. Sudden cardiac arrest prevention represents one of the major potential benefits from health insurance, given the large impact of sudden cardiac arrest on premature death and its potential sensitivity to preventive care. Methods and Results: We conducted a pre–post study with control group examining out‐of‐hospital cardiac arrest (OHCA) among adult residents of Multnomah County, Oregon (2015 adult population 636 000). Two time periods surrounding implementation of the Affordable Care Act were evaluated: 2011–2012 ("pre‐expansion") and 2014–2015 ("postexpansion"). The change in OHCA incidence for the middle‐aged population (45–64 years old) exposed to insurance expansion was compared with the elderly population (age ≥65 years old) with constant near‐universal coverage. Rates of OHCA among middle‐aged individuals decreased from 102 per 100 000 (95% CI: 92–113 per 100 000) to 85 per 100 000 (95% CI: 76–94 per 100 000), P value 0.01. The elderly population experienced no change in OHCA incidence, with rates of 275 per 100 000 (95% CI: 250–300 per 100 000) and 269 per 100 000 (95% CI: 245–292 per 100 000), P value 0.70. Conclusions: Health insurance expansion was associated with a significant reduction in OHCA incidence. Based on this pilot study, further investigation in larger populations is warranted and feasible.